NEED ANALYSIS IN DESIGNING ENGLISH MATERIALS FOR SENDRATASIK STUDENTS - Kamila, Revina; Ristati, Ristati; Usadiati, Wahyuningsih (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2021)
In the process of English teaching and learning at Sendratasik Education Study Program of Lambung Mangkurat University, general English was given and the available English material so far did not include local content of arts related to the students’ needs and interest in their own major. This article aims to present the results of need analysis of English language teaching materials for Sendratasik Education major students at Lambung Mangkurat University based on English for Specific Purposes (ESP) by Hutchinson & Waters (1991). They were expected to be used for developing English materials for students majoring in Sendratasik to cater for their needs in learning English in accordance with their specific major. The data were collected through a questionnaire uploaded in Google Form to be responded by Sendratasik Education major students of Lambung Mangkurat University, Banjarmasin, South Kalimantan. The data obtained were calculated in percentage and the result was analyzed qualitatively. The results might be significantly useful for designers of ESP for they reflected the real needs of Sendratasik Education major students.